2020
DOI: 10.1101/2020.09.10.288720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved interactions required for in vitro inhibition of the main protease of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)

Abstract: The COVID-19 pandemic caused by the SARS-CoV-2 requires a fast development of antiviral drugs. SARS-CoV-2 viral main protease (Mpro, also called 3C-like protease, 3CLpro) is a potential target for drug design. Crystal and co-crystal structures of the SARS-CoV-2 Mpro have been solved, enabling the rational design of inhibitory compounds. In this study we analyzed the available SARS-CoV-2 and the highly similar SARS-CoV-1 crystal structures. We identified within the active site of the Mpro, in addition to the in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…To characterize more inhibitory potentials of proposed 2D nanomaterials against SARS-CoV-2, we set additional coarse-grained long time-scale simulations to elucidate their impact on SARS-CoV-2 M pro . Up to date, researchers have investigated various inhibitors against the M pro , such as peptide-inhibitors [57,95,96], previously FDAapproved drugs [97,98], and herbal components [99]. Our observations from the previous section confirmed that 2D engineered nanomaterials are competent in blocking spike protein.…”
Section: D Nanomaterials Against Sars-cov-2 M Prosupporting
confidence: 67%
“…To characterize more inhibitory potentials of proposed 2D nanomaterials against SARS-CoV-2, we set additional coarse-grained long time-scale simulations to elucidate their impact on SARS-CoV-2 M pro . Up to date, researchers have investigated various inhibitors against the M pro , such as peptide-inhibitors [57,95,96], previously FDAapproved drugs [97,98], and herbal components [99]. Our observations from the previous section confirmed that 2D engineered nanomaterials are competent in blocking spike protein.…”
Section: D Nanomaterials Against Sars-cov-2 M Prosupporting
confidence: 67%
“…To characterize more inhibitory potentials of proposed 2D materials against SARS-CoV-2, we set additional coarse-grained long time-scale simulations to elucidate their impact on SARS-CoV-2 M pro . Up to date, researchers have investigated various inhibitors against the M pro , such as peptide-inhibitors [98-100], previously FDA-approved drugs [101,102], and herbal components [103]. Our observations from the previous section con rmed that 2D engineered nanosheets are competent in blocking spike protein.…”
Section: D Materials Against Sars-cov-2 Proteasementioning
confidence: 66%
“…Specifically, the IC 50 value of UJ against SARS-CoV-2 3CLpro was about 0.94 µM. In molecular modeling, UJ interacted with several core and consensus anchor residues in the active site of SARS-CoV-2 3CLpro (Shitrit et al, 2020;Pathak et al, 2021) (i.e., H163, M165 and E166, G143 and C145, Q189, and P168 in subsites S1, S1′, S2, and S4, respectively) via hydrogen bonding and/or van der Waals interactions, thereby blocking the peptide substrate from accessing the active site. In contrast, the core and consensus residues that Lu, Kae, and Ikae interacted with were M165 and E166, H41, M49 and Q189, and P168 in subsites S1, S2, and S4, respectively, via primarily van der Waals forces.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the core and consensus residues that Lu, Kae, and Ikae interacted with were M165 and E166, H41, M49 and Q189, and P168 in subsites S1, S2, and S4, respectively, via primarily van der Waals forces. In particular, forming hydrogen bonding with H163 and E166 has been regarded as an important feature for potent inhibition of the viral polypeptide cleavage process of SARS-CoV-2 3CLpro (Shitrit et al, 2020).…”
Section: Discussionmentioning
confidence: 99%